Age-Related Effects of Varying Ammonia Concentrations on Hematophysiological Variables in Broiler Chickens - Olanrewaju, H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2009)
This study examined the response of different aged birds of the same genetic strain exposed to ammonia (NH3) at set concentrations on blood gases, electrolytes and acid-base balance under environmentally controlled conditions. The experiment consisted of a 4x4 factorial with a randomized design. The 16 treatments consisted of 4 levels (0, 25, 50 and 75 ppm) of NH3 concentrations and 4 different ages (1-d, 7-d, 14-d and 21-d) of birds. Venous blood samples were collected at the end of each 7 d of atmospheric NH3 exposure. Partial pressure of CO2 (pCO2), pH, Hematocrit (Hct) and Hemoglobin (Hb) increased significantly (p<0.05), whereas partial pressure of O2 (pO2), bicarbonate (HCO3-) and K+ decreased with increasing NH3 concentration compared with 0 ppm. In addition, pO2, pCO2, HCO3-, Hct, Hb, Na+ and Anion gap (Angap) increased significantly (p<0.05), while pH, glucose and corticosterone decreased as bird’s age increased. Ammonia x age interactions were observed for pH, anion gap and HCO3-. Plasma corticosterone concentrations were significantly different for age and were not affected by NH3. The effect of age was more pronounced than that of NH3 on examined variables. This effect of age on examined blood physiological variables improved as the age of birds increased from 1-d to 21-d old birds. Most blood physiological variables of different aged birds of the same genetic strain respond differently to set NH3 concentrations of 0 to 75 ppm and younger birds have a more intense reaction to the NH3 than older birds.